Building evidence for indoor tanning as a behavioral addiction: concerns, problems, and change perceptions are associated with addictive symptoms - Allison Leip; Carolyn J. Heckman; Jerod L. Stapleton (BMC Psychology)
Abstract Background Rates of ultraviolet radiation (UVR)-emitting tanning bed use have declined in the United States over the past decade. However, many young adults continue to indoor tan at rates that put them at risk for melanoma. There is evidence that UVR may impact addiction pathways and some people who use tanning beds experience urges to tan and diminished control over tanning which may be evidence of a behavioral addiction. However, studies have not adequately explored whether excessive tanning continues despite concerns and problems that would be expected with behavioral addiction. This represents an important gap since behavioral persistence in the face of such negative experiences is a hallmark of behavioral addiction. Further, there is a dearth of research exploring change perceptions of excessive tanners. Methods We administered a cross-sectional online survey to women between 18 and 34 years old who reported frequent indoor tanning (at least 10 times) in the past 12 months. Participants completed the 7-item Behavioral Addiction Indoor Tanning Screener (BAITS). T- and chi-square tests were used to compare the association of theoretically informed correlates from conceptual models of behavioral addiction (e.g., concerns and problems) and tanning change/quit perceptions with results from the BAITS (i.e., a positive or negative screen for tanning addiction symptoms). Results Participants were 280 non-Hispanic White women (mean age = 27.5 years (SD = 4.3)) from across the United States (mean number of past 12-month indoor tanning sessions = 40.1 (SD = 42.5)). Frequent indoor tanners with a positive BAITS score had higher mean scores for negative affect, greater worry about getting skin cancer, and more tanning-related problems compared to those with a negative score. A positive BAITS score was also associated with more perceived barriers to quitting tanning, increased interest in getting help to reduce tanning, and a higher number of quit attempts. Conclusions Our findings provide unique evidence for tanning as a behavioral addiction by demonstrating an association between tanning behavioral addiction symptoms with skin cancer concerns, tanning-related problems, and unsuccessful attempts to change. These findings have implications for the design of interventions and support the need for additional research to support the conceptualization of indoor tanning as a behavioral addiction.